ความชุกของภาวะซึมเศร้าหลังคลอด และปัจจัยที่เกี่ยวข้องในมารดาที่ให้นมทารก ณ โรงพยาบาลจุฬาลงกรณ์ - สินาพร วิทยาวนิชชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this cross – sectional descriptive study was to examine the prevalence of postpartum depression (PPD) as well as associated factors among nursing mothers at King Chulalongkorn Memorial Hospital. Data were collected from 313 nursing mothers who come for postpartum follow-up visits (at 4-6 weeks postpartum). Self-report questionnaires include the following general background questionnaire, obstetrics and infant information, a Thai version of Edinburgh Postnatal Depression Scale (EPDS), The Dyadic Adjustment Scale, Personal Resource Questionnaire (PRQ-part II), The Pittsburgh Sleep Quality Index (PSQI), were completed by all subjects. Univariate analysis (e.g. t-test, Chi-Square test, Pearson’s product moment correlation coefficient) was used to examine associated factors with PPD and Multivariate Analysis was used to determine predictors of PPD among this group of women. The results revealed that 16.9% of subjects had depression. Univariate analysis revealed 22 factors significantly associated with postpartum depression, namely: no marital ceremony, currently a student, history of lifetime depression, history of depression during pregnancy, history of premenstrual mood changes, history of caffeine use during pregnancy and postpartum period, history of alcohol use during postpartum period, unwanted pregnancy, third child, vacuum assisted delivery, delayed breastfeeding after delivery, short nipples, current sucking problem, wound pain and other disturbing symptoms in first week after delivery, others disturbing symptoms at present, combined breast milk and formula milk, had other person to take care of the baby at night, poor marital relationship, poor social support, and poor sleep quality. Multivariate analysis revealed only 7 factors significantly associated with postpartum depression, namely; history of lifetime depression, history of caffeine use during pregnancy, birth of the third child onward, assisted delivery, current baby’s sucking problem, had other person to care of the baby at night, and poor sleep quality.